The aftermath of acute kidney injury: a narrative review of long-term mortality and renal function - Gijs Fortrie; Hilde R. H. de Geus; Michiel G. H. Betjes (Critical Care, 2019)
Abstract Acute kidney injury (AKI) is a frequent complication of hospitalization and is associated with an increased risk of chronic kidney disease (CKD), end-stage renal disease (ESRD), and mortality. While AKI is a known risk factor for short-term adverse outcomes, more recent data suggest that the risk of mortality and renal dysfunction extends far beyond hospital discharge. However, determining whether this risk applies to all patients who experience an episode of AKI is difficult. The magnitude of this risk seems highly dependent on the presence of comorbid conditions, including cardiovascular disease, hypertension, diabetes mellitus, preexisting CKD, and renal recovery. Furthermore, these comorbidities themselves lead to structural renal damage due to multiple pathophysiological changes, including glomeruloscleroses and tubulointerstitial fibrosis, which can lead to the loss of residual capacity, glomerular hyperfiltration, and continued deterioration of renal function. AKI seems to accelerate this deterioration and increase the risk of death, CDK, and ESRD in most vulnerable patients. Therefore, we strongly advocate adequate hemodynamic monitoring and follow-up in patients susceptible to renal dysfunction. Additionally, other potential renal stressors, including nephrotoxic medications and iodine-containing contrast fluids, should be avoided. Unfortunately, therapeutic interventions are not yet available. Additional research is warranted and should focus on the prevention of AKI, identification of therapeutic targets, and provision of adequate follow-up to those who survive an episode of AKI.